Representasi Ageism dalam Film Layar Lebar - Nafisa Kahla HT (Jurnal Ilmu Komunikasi, 2022)
Humans will inevitably experience aging characterized by changes in biological, psychological, and social terms. With this change, the elderly get a lot of negative assumptions with all forms of shortcomings in old age. This negative stereotype is unwittingly a form of age discrimination or also known as ageism. Ageism is also often depicted in a film, one of which is the film Old People, so this film was chosen as the object of research. The purpose of this study was to find out how the representation of ageism in the film used Roland Barthes' semiotic analysis. The results showed the presence of negative stereotypes and acts of ageism towards the elderly. It is known through the levels of denotation, connotation, and myth in Barthes's theory.